Mutual Relationship Between Sleep Disorders, Quality of Life and Psychosocial Aspects in Patients With Psoriasis - Nowowiejska, Julia; Baran, Anna; Flisiak, Iwona (Frontiers in Psychiatry, 2021)
Psoriasis is a chronic, autoimmune skin disease affecting about 2–4% of the worldwide population. It is now perceived as a systemic disease because of the complex pathogenesis and multiple comorbidities. It leads to decreased quality of life and productivity of patients. Nowadays, sleep disorders are investigated as well in relation to psoriasis as another possible comorbidity. This review focuses on possible negative effects of sleep deprivation, decreased quality of life, and psychosocial status in patients with psoriasis and highlights their mutual, complex relationship of divergent consequences. The relationship between sleep disorders and psychosocial status in patients with psoriasis is bidirectional and resembles a vicious circle, one abnormality triggering the other. Sleep disorders additionally increase the risk of metabolic and psychiatric diseases in psoriatic patients who are already at increased risk of developing such disorders. There should be measures taken to screen patients with psoriasis for sleep disorders in order to diagnose early and treat.